2001
DOI: 10.1182/blood.v97.6.1584
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction in patients with sickle cell disease is related to selective impairment of shear stress–mediated vasodilation

Abstract: Interactions between the endothelium and erythrocytes may contribute to the vascular complications of sickle cell disease (SCD). Endothelium-derived nitric oxide (NO) plays a major role in the regulation of vasomotor tone in response to wall shear stress (WSS) variations and pharmacologic stimuli. However, little is known about endothelial NO production in patients with steadystate SCD. We investigated endothelial NO production in response to flow or vasoactive agonists in 16 homozygous patients with steady-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
150
3

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 176 publications
(162 citation statements)
references
References 31 publications
8
150
3
Order By: Relevance
“…We found that methacholine-induced forearm blood flow response was preserved in HbSS, while others have demonstrated a heightened response to acetylcholine [7,9]. The reasons for these apparently discrepant findings are not immediately clear, but could relate to differences in the study populations.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…We found that methacholine-induced forearm blood flow response was preserved in HbSS, while others have demonstrated a heightened response to acetylcholine [7,9]. The reasons for these apparently discrepant findings are not immediately clear, but could relate to differences in the study populations.…”
Section: Discussioncontrasting
confidence: 55%
“…Transgenic murine models of sickle cell disease have shown greater basal NO production with a greater rise in blood pressure with NOS inhibition, although results regarding NOS expression are controversial [5,6]. In humans with HbSS, the contribution of NO to increased basal flow and reduced peripheral resistance is unclear [7]. Our findings of greater resting forearm blood flow with greater absolute and relative flow decreases with NOS inhibition supports increased basal NO production contributes to the regulation of basal tone and tissue perfusion in HbSS in the steady state.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relevance of these data, of course, lies in the fact that humans with sickle disease are known to be biodeficient in NO [13,14]. Thus, the implication of this study is that the NO-deficient status of patients with sickle cell anemia, in the context of their already existing inflammatory state [7], probably increases their risk for coagulation activation, TF being the trigger of such activation.…”
Section: Discussionmentioning
confidence: 77%